Implementasi Belajar Mahasiswa pada Mata Kuliah Ilmu Sosial Dan Budaya Dasar (ISBD) di Program Studi TIK di Lingkungan STKIP Pesisir Selatan - Handayani, Revi; Mayeni, Riska; Wiwita, Risma; Sefrinal, Sefrinal; Efendi, Efendi (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2024)
The implementation of student learning in the Basic Social and Cultural Sciences (ISBD) course in the ICT Study Program in the STKIP Pesisir Selatan environment has been carried out. From this research, researchers saw that there were socio-cultural changes, sensitivity towards others, and feelings of empathy were reduced. Making fellow students less sensitive, lacking interaction and acting indifferent. Because it focuses on the use of increasingly sophisticated technological media. Even the expected achievements in the ISBD course have not yet been achieved. In particular, the ICT study program in the STKIP Pesisir Selatan environment is the main locus and is an accentuation and will be elaborated more deeply by researchers. This type of research is qualitative research carried out by observing phenomena that often occur in the campus environment. This type of research is qualitative research carried out by observing phenomena that often occur in the campus environment, linked to existing theories as a result of previous research and will be explained in descriptive form. The results of this research are an applicable form of Prevention. So far, there are many things that we want to express as teachers, namely that the phenomenon of being sensitive to other people has been reduced in this case, so the achievements to be achieved in each sub-chapter of ISBD material are not expressed as they should be.